2019
DOI: 10.1186/s13046-019-1230-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined blockade of MEK and PI3KCA as an effective antitumor strategy in HER2 gene amplified human colorectal cancer models

Abstract: Background Targeting the epidermal growth factor receptor (EGFR) either alone or in combination with chemotherapy is an effective treatment for patients with RAS wild-type metastatic colorectal cancer (mCRC). However, only a small percentage of mCRC patients receive clinical benefits from anti-EGFR therapies, due to the development of resistance mechanisms. In this regard, HER2 has emerged as an actionable target in the treatment of mCRC patients with resistance to anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Then, the hub lncRNAs function was evaluated by GO and KEGG analyses. The results demonstrated that the MAPK signaling pathway and protein biological regulation were the most relevant functional, which was consistent with previous studies (Belli et al, 2019 ; Schumacher et al, 2019 ; Vitiello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Then, the hub lncRNAs function was evaluated by GO and KEGG analyses. The results demonstrated that the MAPK signaling pathway and protein biological regulation were the most relevant functional, which was consistent with previous studies (Belli et al, 2019 ; Schumacher et al, 2019 ; Vitiello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…With the aim of getting a better understanding of the mechanisms of resistance to HER2-directed and EGFR-directed therapies, it has been recently reported that increased expression of MUC1 and MET , decreased expression of PTEN , and an activating mutation in PIK3CA is accompanied with HER2 -amplified in mCRC. These findings strongly highlight the molecular heterogeneity of the resistance to anti-EGFR therapy [39,46,49,50,51,52].…”
Section: Acquired Resistance To Anti-egfr Treatment In Crc Patientsmentioning
confidence: 88%
“…These phenomena result from different cell signalization pathways in the form of a downstream of phosphorylations/dephosphorylations through the epithelial cell when the HER2 receptor is activated. The phosphoinositide 3-kinase/Protein Kinase B (PI3K/AKT) [23] and the RAF/MEK/MAPK pathways are the most solicited [24]. The detection of HER2 in particular is very relevant because breast cancers involving HER2 protein overexpression, also known as HER2-positive (HER2+) breast cancer, tend to be more aggressive with a more rapid progression and a higher propensity to come back in comparison with HER2-negative (HER2-) ones [25].…”
Section: Introductionmentioning
confidence: 99%